Influence of Confined Phonons on the Hall Coefficient in a Cylindrical Quantum Wire with an Infinite Potential (for Electron–acoustic Optical Phonon Scattering) - Ngoc Thang, Pham; Thai Hung, Le; Long, Do Tuan; Quang Bau, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
This paper studies the influence of confined acoustic phonons on the Hall coefficient (HC) in a cylindrical quantum wire (CQW) with an infinite potential (for electron – confined acoustic phonons scattering). The paper considers the case where CQW is placed in a perpendicular magnetic field , a constant electric field  and an intense electromagnetic wave . By using the quantum kinetic equation for electrons interacting with confined optical phonons (COP), analytical expressions for HC are obtained. The application of numerical calculations to GaAs/GaAsAl cylindrical quantum wire shows that the HC depends on magnetic field B, temperature T, frequency Ω and amplitude E 0 of laser radiation and on quantum indices m 1 and m 2 characterizing the phonon confinement. This influence is due to the quantum indices m1 and m 2 which increase the Hall coefficient by 2.3 times in comparison with the case of unconfined phonons. When the quantum numbers m 1 and m 2 go to zero, the result is the same as in the case of unconfined phonons.